Glagolski internacionalizmi v slovenščini in nemščini ter njihova vezljivost s kontrastivnega vidika - Krevs Birk, Uršula (Jezik in slovstvo, 2022)
The article deals with international verbs in German and Slovene, in particular with the semantic and valency structures of the selected pairs of verbs. First, the role of the international words contained in the CEFR is discussed as well as compared with "global" words present in several languages of the world and concerning a global topic such as the recent pandemic. Second, the criteria for recognizing international lexemes are presented. If a word is to be considered an international lexeme it has to be semantically equivalent in at least three languages, two of which are not genetically related. Partial semantic equivalence can generate pairs of false friends. A number of pairs of international verbs differ in terms of international verbs depends also on the variability of a given German lexeme in the different standard varieties of German.
Keywords: contrastive analysis; German; glagolski internacionalizmi; international verbs; kontrastivna analiza; nemščina; Slovene; slovenščina; valency; vezljivost